The concept of patriotism and struggle against imperialism in the selected poems of Mehmet Akif Ersoy and W. B. Yeats - Ali Yigit, (Pusat Pengajian Bahasa dan Linguistik, FSSK, UKM, 2012)
In the early twentieth century, imperialism was living its hey-day, with almost more than half the world as the colony of the European imperial powers particularly that of Britain and France. Realizing the destruction and damage that the colonizers had done to their countries, a wide range of people from politicians to writers, poets and ordinary people started to move against the colonizers. In India, Africa, Middle East and even in Europe there were a lot of people who opposed imperialism and colonization. Mehmet Akif Ersoy from Turkey and William B. Yeats from Ireland represent the literary side of the struggle against imperialism. Both these poets lived in the same era (late 19th and early 20th centuries) and they embarked on a struggle against imperial powers with their pen. Mehmet Akif gave material and spiritual support to the Anatolian people with his writings against the occupation of the Allies after WW II. In order to regain the Irish their cultural independence, Yeats tried to show ways of bearing up the British Imperialism which had been dominant in Ireland for centuries by making use of Irish national cultural values and folklore. This study aims to explore and comparatively evaluate the concept of patriotism and the struggle against imperialism in “The March of Independence” by Ersoy and “Easter 1916” by Yeats.